2017
DOI: 10.1002/jmv.24949
|View full text |Cite
|
Sign up to set email alerts
|

Group A rotaviruses circulating prior to a national immunization programme in Nigeria: Clinical manifestations, high G12P[8] frequency, intra‐genotypic divergence of VP4 and VP7

Abstract: Nigeria having approximately 50 000 Rotavirus A (RVA) deaths annually is yet to introduce RVA vaccine into routine national immunization; therefore surveillance of RVA strains circulating before vaccine introduction is essential in evaluating impact of the intervention. Stool samples and sociodemographic data of diarrhoeic children, <5 years were collected between August 2012 and December 2013. While a high prevalence of RVA infection (47.6%; 49/103) was observed by quantitative reverse transcription real time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…The evolutionary rate observed in our study hovers around the global rate previously reported for rotavirus genotype G12 in 2010 (Matthijnssis et al, 2010), this shows that the African strains have a steady mutation rate but possess the potential to diversify rapidly through molecular evolution. This can also be due to repeated outbreaks in populated communities, giving opportunity for recombination and reassortment (Gomez et al, 2014, Japhet et al, 2018. The time to most recent common ancestor T MRC, was calculated to be 16.8 years, 95% HPD (15.0 -25.54), dating back to around mid-1996.…”
Section: Resultsmentioning
confidence: 99%
“…The evolutionary rate observed in our study hovers around the global rate previously reported for rotavirus genotype G12 in 2010 (Matthijnssis et al, 2010), this shows that the African strains have a steady mutation rate but possess the potential to diversify rapidly through molecular evolution. This can also be due to repeated outbreaks in populated communities, giving opportunity for recombination and reassortment (Gomez et al, 2014, Japhet et al, 2018. The time to most recent common ancestor T MRC, was calculated to be 16.8 years, 95% HPD (15.0 -25.54), dating back to around mid-1996.…”
Section: Resultsmentioning
confidence: 99%
“…At country level in West Africa, before vaccine introduction, Ghana reported G1P [8] (20%) as the predominant genotype [17], but others genotypes such as G6P [6] was found to be medically important in Burkina Faso [18], G12P [8] in Côte d'Ivoire [19] and G4P [8] and G12P [8] in Nigeria [20,21]. During the post vaccine period, Ghana reported G1P [8] as the fourth common genotype detected with a rate of 8.0% [17].…”
Section: Discussionmentioning
confidence: 99%
“…Commonly detected at low rates in Africa, over the past decade, G12P [8] has been isolated as a predominant genotype in some countries such as Côte d'Ivoire and Nigeria in the pre-vaccination period [19,21], and Ghana in the post-vaccination period [17]. Also, according to some studies, G12P [8] may come from a reassortment between human and pig rotavirus strains [31].…”
Section: Discussionmentioning
confidence: 99%
“…At country level in West Africa, before vaccine introduction, Ghana reported G1P [8] (20%) as the predominant genotype (18), but others genotypes such as G6P [6] was found to be medically important in Burkina Faso (19), G12P [8] in Côte d'Ivoire (20) and G4P [8] and G12P [8] in Nigeria (21,22). During the post vaccine period, Ghana reported G1P [8] as the fourth common genotype detected with a rate of 8.0% (18).…”
Section: Discussionmentioning
confidence: 99%